Candida albicans in Association with Pathogenic Bacteria to Form Mono and Polymicrobial Biofilms - Dahi, Rawan Ahmed; AL-YASIRI, Mohammed Hashim; Al-Hatmi, Abdullah M.S. (University of Thi-Qar Journal of Science, 2025)
Abstract Biofilm formation by the accumulation of various pathogens may be responsible for chronic and acute human infections. This research aimed to explain the role of Candida albicans in biofilm formation with pathogenic bacteria isolated from clinical samples. Ninety clinical samples were collected to isolate pathogenic bacteria and Candida albicans. The isolation and identification of these pathogens were performed using selective media and the VITEK 2 system. Flat-bottom microtiter plates were used to evaluate the ability of all isolates to form biofilms in case of monomicrobial and polymicrobial species. Three pathogenic bacteria, including Staphylococcus aureus (n=8), Pseudomonas aeruginosa (n=8), and Escherichia coli (n=4), as well as C. albicans (n=20), were isolated. All isolates were submitted to evaluate their ability to form monomicrobial and polymicrobial biofilms. In the case of monomicrobial species, C. albicans (100%) and bacterial species (80%) showed a high percentage of biofilm formation. However, C. albicans was prepared to make an adherence phase for each one of S. aureus, P. aeruginosa, and E. coli. In this experiment, all bacterial isolates improved their ability to form polymicrobial biofilms. in contrast, some bacterial isolates reduce their ability for forming polymicrobial biofilms if bacterial isolates are used as an adherence phase. In conclusion, the replacement of adherence phase of the polymicrobial biofilm causes either an increase or a decrease in the ability of organism to form a biofilm when compared to monomicrobial biofilms.